An investigation of factors affecting technology acceptance and use decisions by Australian allied health therapists - Schaper, Louise; Pervan, Graham (HICSS, 2007)
The research reported in this paper describes the development, empirical validation and analysis of a model of technology acceptance by Australian occupational therapists. The study described involved the collection of quantitative data through a national survey, with over 2000 responses and a longitudinal case study within the community health sector. Results provide qualitative and quantitative support for the proposed model and demonstrate the inadequacy of traditional models of technology acceptance when applied to the health sector. This work extends technology acceptance studies into new realms of the health sector and highlights the need for a broadening of health IT research, and particularly technology acceptance studies, to encompass a more holistic and inclusive view of those who work in healthcare in order to gain a greater understanding of its complexities and how IS implementation success can be enhanced in this arena.